THE IMPORTANCE OF DANCE AS A CONTENT OF PHYSICAL EDUCATION AT SCHOOL - dias, Plinio Fabricio; Antônio Araújo Filho, Marcos (RENEF, 2022)
The aim of this article was to analyze the proposal for teaching dance in the Physical Education school curriculum and to know and value the expressive possibilities of the body itself. The research method was qualitative, the research was classified as explanatory. The studied public of that research was composed of 04 Physical Education teachers, who work in the area for more than five years. For data collection, a structured interview was used. . Data were analyzed using descriptive statistics using percentage values. The results presented according to the questionnaire reveal that most Physical Education teachers believe the role of dance in their classes is important, they believe in the benefit it provides, but some believe that certain rhythms can be an obstacle when applying the content. as there are students of different religions and races who may feel uncomfortable. In conclusion, dance contributes to the teaching-learning process, through this art one acquires a gradual development, with improvement in school performance, positive changes in behavior, among many other aspects